Measuring Nonmonetary Utilities in Uncertain Choices: The Ellsberg Urn - Smith, Vernon L. (Quarterly Journal of Economics, 1969)
Introduction, 324. — I. The Ellsberg problem, 326. — II. Probabilistic interpretation, 326. — III. Utility interpretation, 327. — IV. Measuring nonmonetary utility, 328.